Littleness of the Culture in the Middle Europe for Example Slovensko a jeho život literárny (Slovakia and Her Literary Life) by Jozef Miloslav Hurban ). - CHRISTIAN PRUNITSCH (Slovenska Literatura, 2005)
“Littleness” appears as relevant for certain culture when it is determined by its own or foreign texts. This determination in an intercultural contact behaves as an explicit or implicit valuing act approached within the positions of superiority, inferiority, identity a alterity, translativity, singularity, as well as ancienity and juvenility. In the specific situation of the Slovak national revival an essay by Jozef Miloslav Hurban Slovensko a jeho život literárny (Slovakia and Her Literary Life) is an important text of apologetic legitimating strategy of Slovak culture in the Central European context. Hurban uses mostly the term “vitality of Slavs”, which had been attributed to them since Herder, and in comparison with ancient European cultural nations he creates a picture of a dynamic Slovak young man, smartly walking towards a new epoch. Both an argument of time and an argument of placing were presented to stress the central position of Slovaks in the project of renewing the Central Europe. The argument of placing was usually presented in the glorification of High Tatras. In the changed constellation of the 20th century motivating power of important ideological potential of the essay was weakened. Hurban’s suggested a concept of future Slovak culture, also outlined with the aim against Czechs and Magyars, resisted only to a very limited extent the pressure coming from the Central European constellation after 1848, as also proved in the final passages of his essay.